The Raven tower - Leckie, Ann (Orbit, an imprint of Hachette Book Group, 2019)
"Following her record-breaking run in science fiction, Ann Leckie, winner of the Hugo, Nebula, Arthur C. Clarke and Locus Awards, brings her immense talent to an epic fantasy novel about the hidden forces that guide our fates. Having helped win a war at great cost in human lives and to its own power, the god known as the Raven of Iraden was forced to continue to fulfill its commitment to its followers and slowly regain its strength through the steady flow of prayers and sacrifices which are the source of all the gods' powers. Centuries into that toil, a usurper to the throne of Iraden has discovered the Raven's weakened state and sets in motion a plot to gain the favor of younger, stronger gods in a bid to consolidate his power. But the Raven of Iraden is more resilient than its enemies have accounted for, and with the help of some unlikely allies it may still return to glory" --